Evaluation of nutritional, anti-nutritional and mineral content of amaranths species grown in Gamo and Konso zone, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
Amaranth (Amaranthus sp.) is an underutilized pseudo-cereal with excellent nutritional and functional properties. The nutritional compositions, anti-nutritional and mineral content of two Amaranth species were evaluated by using standard procedures. Completely Randomized Design (CRD) was used for nutritional, anti-nutritional and mineral content with two treatments and five replications. The nutritional compositions of Amaranthus cruentus and Amaranthus hypochondriacus were shown a significant difference (p